Understanding The Synergy Between Optic Technicians And Nurses In Eye Health (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the symbiotic relationship between optic technicians and nurses in the realm of eye health, highlighting the synergistic collaboration that enhances patient care outcomes. Optic technicians, proficient in diagnostic tests and technical support, complement the clinical expertise of nurses in providing comprehensive eye care services.